Uslūb al-Kināyah Kaẓāhirah Uslūbīyah Hāmah Fī al-Qur’an al-Karīm - Sukamto Said (Al-Jami'ah: Journal of Islamic Studies, 2001)
One of the miracles of Qur'an is its wording. Qur'an was revealed in Arabic for the people who had a great on language aesthetics (literature) to convey the message and use various literaly styles. One of them is kinayah.  This article examines the issue of the literary style in Qur'an' kinayah, which is multipurpose. It can be used to depict either human interest or godhead. Kinayah is used, among other things, because of the restriction on language to express certain ideas. As a holy book for human that is valid forever, Qur'an uses kinayah to create new meanings, because the characteristic of kinayah is its possibility to be undersiood from "stem-meaning" (al-ma'na al malzum)point of view and from ”derivative-meaning”(al-ma,na al-lazim)  Point of view.  The derivative meaning that emerged by kinayah, everyone has distinct perceptions based on their own reagolrs. There is a plural sense here that enables the understanding on Qur'an as well as means as a symbol of Qur'anic dynamism all the time.[Salah satu kemukiizatan al-Qur'an adalah redaksi yang digunakannya. Al-Qur’an yang diturunkan  dalam bahasa Arab pada masyarakat yang mempunyai perhatian besar pada keindahan bahasa  (sastra) dalam menyampaikan Pesan-Pesannya, menggunakan gaya bahasa yang sangat variatif. Di antaranya adalah gaya bahasa kinayah. Artikel ini membicarakan fenomena gaya bahasa kinayah dalam al-Qur'an yang digunakan untuk berbagai macam tujuan, baik untuk mengungkapkan masalah-masalah kehidupan manusia, maupun masalah-masalah yang berkaitan dengan sifat ketuhanan. Gaya bahasa kinayah digunakan , antara lain, karena keterbatasan bahasa unfuk mengungkapkan gagasan-gagasan tertentu. sebagai kitab petunjuk bagi manusia yang berlaku sepanjang masa sejak diturunkan, al-Qur'an memanfaatkan gaya bahasa kinayah untuk melahirkan makna-makna baru, sebab ciri bahasa kinayah adalah kemungkinannya unfuk dapat dipahami dari sisi "arhasal" (al-ma,naalmalzum)  dan sisi "arhbaflr" (al-ma'na al-azim) sekaligus.  Tentang arti baru yang ditimbulkan oleh bahasa kinnyah ini, antara sesorang dengan yang lain dapat berbeda .atas dasar alasan masing-masing. Di sini terletak pluralitas makna yang memungkinkan perkembangan pemahaman terhadap al-qur’an, sekaligus juga merupakan tanda dinamika al-Qur'an, yang berlaku sepanjang masa, itu sendiri.